Cardiac Sympathetic Afferent Denervation Protects Against Ventricular Arrhythmias by Modulating Cardiac Sympathetic Nerve Activity During Acute Myocardial Infarction - Zhou, Mingmin (Med Sci Monit, 2019)
BACKGROUND: Augmented cardiac sympathetic afferent reflex (CSAR) plays a role in enhanced sympathetic activity. Given that a strategy for abolishing augmented CSAR-induced sympathetic activation may be beneficial for protecting against ventricular arrhythmias (VAs) triggered by acute myocardial infarction (AMI), we investigated whether cardiac sympathetic afferent denervation (CSAD) could protect against VAs by modulating cardiac sympathetic nerve activity in an AMI dog model. MATERIAL/METHODS: Twenty-two anesthetized dogs were assigned to the CSAD group (n=9) and the sham group (n=13) randomly. CSAD was produced by epicardial application of resiniferatoxin. Heart rate variability (HRV), ventricular action potential duration (APD), APD dispersion, beat-to-beat variability of repolarization (BVR), effective refractory period (ERP) of ventricles, ERP dispersion, plasma norepinephrine (NE) concentration, and left stellate ganglion (LSG) neural activity were determined at baseline and after CSAD. We designed an AMI model by occluding the left anterior coronary artery, and performed analysis of VAs for 60 minutes using electrocardiography. Then, levels of c-fos and nerve growth factor (NGF) were determined. RESULTS: Relative to baseline values, CSAD prolonged ERP and APD of ventricles, increased HRV, decreased APD dispersion, BVR, ERP dispersion and serum NE concentration, and attenuated LSG activity in the CSAD group. AMI triggered a remarkable increase in LSG activity and function but decreased the HRV of the sham group animals relative to the CSAD group. Moreover, the CSAD group had higher levels of VAs relative to the sham group. This was accompanied by a corresponding decrease in proteins quantities of NGF and c-fos in the CSAD group in the LSG after AMI compared to the sham group. CONCLUSIONS: CSAD can suppress LSG neural activity, hence enhance the electrophysiological stability and protect the heart from AMI-triggered VAs.